Decentralize power sharing control strategy in islanded microgridsDecentralize power sharing control strategy in islanded microgrids - Mubashir Hayat Khan; Shamsul Aizam Zulkifli; Erum Pathan; Elhassan Garba; Ronald Jackson; Haider Arshad (Institute of Advanced Engineering and Science, 2020)
Droop control technique is one of the renowned techniques which does not need any communication connection between distibuted generations (DG), hence the cost, as well as the reliability of the microgrid (MG) system can be reduced. MG is operated in two modes as their functionality and structure is concern. These are the grid connected or islanded (stand-alone) mode. DGs operating values may have different ratings of voltage, power and line impedance. The power sharing in these operatng conditions is not shared equally by all DGs connected in the system and also during load changes conditions power sharing accuracy is difficult to achieve. In this paper, a droop power control is used to balance the power sharing in islanded mode. As from the results, the active power sharing is equally shared from all DGs connected in the microgrid system. However, reactive power sharing accuracy always disturbed when there is impedance mismatch among the different DG feeders. The accuracy is done by monitoring the effects when load changes for low load to high load or vice versa. The proportional integral (PI) controller has been used to minimize the reactive power errors. At the end, the power droop is capable to share power accurately and results prove the stability and reliability of the proposed technique.